Legality of Electronic Signatures: A Comparative Study Between Indonesia and Singapore - Adhi Ningtias Nugraha; Salim Hs; Aris Munandar (International Journal of Educational and Life Sciences, 2025)
This study evaluates the user experience of the ShopeePay digital wallet application using the User Experience Questionnaire (UEQ) method. The research assessed six dimensions of user experience: attractiveness, clarity, efficiency, reliability, stimulation, and novelty, using a questionnaire completed by 100 active users aged 18-35. Results revealed that ShopeePay provides a positive user experience, with the highest scores for attractiveness (4.43) and clarity (4.45), indicating an appealing and user-friendly design. Despite strong performance, issues such as less intuitive navigation and limited personalization options were identified. Recommendations include improving navigation structure, adding features such as expense analysis and reminders, and offering personalization options to enhance user satisfaction.